Preparation method and application of Fe2O3 doped SnO2 nanofiber gas sensor
Through the preparation and temperature modulation technology of Fe2O3-doped SnO2 nanofiber gas sensor, the limitations of existing SnO2 sensors in terms of selectivity and sensitivity are solved, and efficient identification and monitoring of n-propanol is achieved, and the performance and stability of the sensor are improved. sex.
Patent Information
- Application Number
- CN202411485534.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-14
AI Technical Summary
The existing SnO2 gas sensors have limitations in selectivity and sensitivity, making it difficult to effectively identify and monitor harmful gases such as n-propanol, and there is a problem of cross-interference.
The preparation method of Fe2O3-doped SnO2 nanofiber gas sensor is adopted to synthesize nanofibers through electrospinning technology and calcinate them in the air. The sensing performance is optimized in combination with temperature modulation technology to improve the recognition ability of n-propanol.
High sensitivity and selective identification of n-propanol are achieved, cross-interference is reduced, and the performance stability and reliability of the sensor are improved, providing new ideas and methods for the detection of environmental pollutants.
Smart Images

Figure CN119310148A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas sensors, and more specifically to a preparation method and application of a Fe2O3-doped SnO2 nanofiber gas sensor. Background Art
[0002] With the acceleration of industrialization and the improvement of people's living standards, environmental pollution and safety issues have become increasingly prominent. Gas sensors, as an important tool for detecting and monitoring harmful gases, have received widespread attention. n-Propanol (C3H8O) is a common organic solvent and fuel. Its volatility and flammability make it frequently used in industry and daily life, which also increases the demand for its accurate monitoring. Therefore, the development of highly sensitive and highly selective gas sensors is of great significance to ensure environmental safety and public health.
[0003] Tin oxide (SnO2), as a widely used semiconductor gas sensing material, has attracted attention due to its excellent electrical properties, chemical stability and good temperature sensitivity. However, a single SnO2 gas sensor has certain limitations in selectivity and sensitivity. In order to improve the performance of the sensor, researchers began to explore methods through material modification, among which doping with iron oxide (Fe2O3) is considered to be an effective approach. Doping with Fe2O3 can not only improve the conductivity of SnO2, but also regulate its surface properties, thereby enhancing its sensitivity to specific gases. As an effective sensing enhancement strategy, temperature modulation technology can significantly improve the response to specific gases and reduce cross-interference by adjusting the operating temperature of the sensor, thereby improving the selectivity and sensitivity of the sensor. Summary of the invention
[0004] In order to overcome the above-mentioned defects of the prior art, the present invention provides a preparation method and application of a Fe2O3-doped SnO2 nanofiber gas sensor.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing a Fe2O3-doped SnO2 nanofiber gas sensor, comprising:
[0007] (1) Preparation of Fe2O3-doped SnO2 nanofibers
[0008] The method comprises: synthesizing nanofibers by using electrostatic spinning technology, and calcining in air to obtain the nanofiber gas-sensitive material;
[0009] Wherein, the electrospinning solution comprises tin salt, iron salt and polymer.
[0010] Preferably, in the electrospinning solution, the tin salt is preferably at least one of stannous chloride, stannous oxalate, tin tetrachloride or stannous sulfate; the iron salt is preferably at least one of ferric chloride, ferric sulfate and ferric nitrate; and the polymer is preferably at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile or polystyrene.
[0011] Preferably, in the electrospinning solution, the mass ratio of the tin salt, the iron salt and the polymer is 0.6:0.5:0.9.
[0012] Preferably, the electrospinning solution further comprises an organic solvent;
[0013] Preferably, the organic solvent is at least one of N,N-dimethylformamide, polyvinyl alcohol or formic acid.
[0014] Preferably, the voltage of the electrospinning is 16-20 kV, the distance between the needle and the collector is 10-20 cm, and the feeding speed is 0.0002-0.0004 mm / s.
[0015] Preferably, the calcination temperature is 450-550°C, the time is 1-3h, and the heating rate is 1-3°C / min.
[0016] (2) Fabrication of gas sensors
[0017] Preferably, Fe2O3-doped SnO2 nanofibers (Fe2O3-SnO2) are used as gas sensitive sensing materials.
[0018] Furthermore, according to the requirements of the sensitive material properties and the preparation method, six-pin nickel-chromium is selected as the sensor substrate.
[0019] Furthermore, the sensitive material is usually deposited on the substrate in the form of a thin film. During the preparation process, parameters such as temperature, atmosphere and pressure must be controlled to ensure the uniformity and consistency of the sensitive film layer.
[0020] Furthermore, preparation of polar electrodes: processing polar electrodes on the sensitive film layer to provide input and output of current and voltage.
[0021] Furthermore, encapsulation protection: the prepared sensitive element is encapsulated to protect the sensitive film layer from interference from the external environment and impurities.
[0022] Further, connection and testing: connecting and fixing the sensitive element to the external circuit and performing relevant tests. The testing process may involve measuring resistance, current and voltage, and evaluating the response to the target gas.
[0023] Furthermore, it should be noted that various parameters and conditions need to be strictly controlled during the preparation of the element to ensure the stability and reliability of the sensitive performance. In addition, in order to obtain better sensing performance, the performance of the sensor element can be further improved by regulating factors such as temperature, pressure, atmosphere, etc. during the preparation process, as well as optimizing the material and structural design.
[0024] Preferably, a ceramic sheet is selected as the main structure of the sensor, the sensing element is mainly supported by a six-pin base, the gold electrode on the front of the heating ceramic plate is used as a test electrode, and the RuO2 resistor on the back is used as a heating electrode to provide the required operating temperature for the target gas test.
[0025] Furthermore, when manufacturing the sensor, it is necessary to select a translucent nanofiber membrane of appropriate size and thickness as the material of the gas-sensitive sensor element. In general, the differences in the materials of different gas-sensitive sensor elements are mainly reflected in their sensitive properties and their applications in sensor manufacturing. In practical applications, it is crucial to select suitable gas-sensitive materials according to the specific needs of the sensor. It is worth noting that in order to ensure the stability of the experiment, the sensors that have been manufactured need to be subjected to a stable aging treatment, which generally lasts for 12-24 hours under dry conditions for proper storage. After completing the corresponding steps, the gas sensor can perform the corresponding experimental operations.
[0026] Preferably, the gas sensor is a n-propanol gas sensor.
[0027] (3) Parameter control of temperature modulation technology
[0028] Including adjustment of frequency, duty cycle and voltage parameters.
[0029] Preferably, a Keithley 6487 picoammeter is used as voltage source and current reader, applying a membrane voltage of 5 V to the transducer and recording two values per second.
[0030] Preferably, a RIGOL DP832A is used to apply a square wave pulse heating voltage to the resistance wire, and the parameters are as follows: low voltage 0V, high voltage 6.5V and 50% duty cycle; frequency adjustment range: 0.01Hz-0.05Hz.
[0031] n-Propanol gas-sensitive performance test
[0032] Preferably, the gas sensor is a n-propanol gas sensor.
[0033] Preferably, the sensing measurements are performed in a closed glass container (500 mL) equipped with appropriate gas flow inlet and outlet. Temperature modulated sensing of the detected gas is performed in dry air, and each measurement is repeated three or more times.
[0034] Preferably, in the present invention, a ceramic sheet is selected as the main structure of the sensor, the sensing element is mainly supported by a six-pin base, the gold electrode on the front of the heating ceramic plate is used as a test electrode, and the RuO2 resistor on the back is used as a heating electrode to provide the required operating temperature for the target gas test.
[0035] Identification of n-Propanol Gas
[0036] The present invention provides a method for identifying n-propanol gas.
[0037] Preferably, LDA (Linear Discriminant Analysis) is used;
[0038] Preferably, the gas is identified and analyzed using quantitative analysis.
[0039] Preferably, the manufactured sensor needs to be subjected to a stable aging treatment, generally by being properly stored under dry conditions for 12-24 hours.
[0040] Technical effects and advantages of the present invention:
[0041] The present invention aims to controllably prepare Fe2O3-doped SnO2 nanofiber gas sensors, and optimize the sensing performance by temperature modulation method, so as to achieve the purpose of successfully identifying n-propanol. By characterizing the structure and properties of the material, and the influence of temperature on the gas response characteristics, the working mechanism of the modified material is deeply explored, providing new ideas and methods for the application of Fe2O3-doped SnO2 nanofiber gas sensors in identifying and detecting environmental pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 : Schematic diagram of the technical solution of the invention.
[0043] Figure 2 : Material characterization of Fe2O3 doped SnO2 nanofibers, (a) SEM image of Fe2O3-SnO2; (bc) TEM images of Fe2O3-SnO2.
[0044] Figure 3 : Performance test diagram of Fe2O3 doped SnO2 nanofiber gas sensor, (a) response of Fe2O3-SnO2 sensor to 100ppm n-propanol at different operating temperatures; (b) relative response bar graph of Fe2O3-SnO2 sensor to 100ppm n-propanol and other interfering gases at 250℃.
[0045] Figure 4: Performance test diagram of Fe2O3 doped SnO2 nanofiber gas sensor, (a) real-time response curve of Fe2O3-SnO2 sensor to different concentrations of n-propanol; (b) relative response and linear fitting curve between different concentrations of n-propanol.
[0046] Figure 5 : Performance test diagram of Fe2O3 doped SnO2 nanofiber gas sensor, (a) real-time response curve of Fe2O3-SnO2 sensor to 100ppm n-propanol at 250℃; (b) real-time response curve of Fe2O3-SnO2 sensor to 100ppm n-propanol within 22 days.
[0047] Figure 6 : Real-time characteristic response curve of Fe2O3-SnO2 sensor to alcohol gas under temperature modulation, (a1-a4) 0.01Hz; (b1-b4) 0.02Hz; (c1-c4) 0.03Hz; (d1-d4) 0.04Hz; (e1-e4) 0.05Hz.
[0048] Figure 7 : Recognition results of Fe2O3-doped SnO2 nanofiber gas sensor for n-propanol, (a) 0.01Hz; (b) 0.02Hz.
[0049] Figure 8 : Quantitative analysis diagram of n-propanol gas identification, (a) relationship between the n-propanol gas response current characteristic curve and different concentrations; (b) linear fitting relationship between relative response value and different concentrations. DETAILED DESCRIPTION
[0050] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] The technical solution of the present invention mainly includes the following parts:
[0052] Embodiment 1
[0053] (I) Preparation of Fe2O3-doped SnO2 nanofibers
[0054] Preparation of Fe2O3-doped SnO2 nanofibers: First, 0.6 g SnCl2·2H2O, 0.5 g Fe(NO3)3·9H2O and 0.9 g PVP(M w=1300000) and 4.5mL DMF, slowly stirred for 6-8h, the magnetic speed was kept at 80rpm / min, and a uniform electrospinning precursor solution was obtained. The specific conditions of electrospinning are as follows: the electrospinning precursor solution is transferred to a 5mL syringe equipped with an 18G needle. The working distance between the needle tip and the receiver (conductive tin foil is used in this experiment) is kept at 15cm, a high voltage of 18kV is applied, and the pushing speed is 0.0003mm / s.
[0055] After 2-3 hours of electrospinning, a nanofiber precursor film evenly spread on the tin foil was obtained, which was dried and calcined in a muffle furnace, maintaining a calcination temperature of 500°C for 2 hours and a heating rate of 2°C / min. After the above steps, Fe2O3-doped SnO2 nanofibers were finally obtained. Figure 2 The material properties of Fe2O3 doped SnO2 nanofibers are shown in Figure 1. First, the Fe2O3 doped SnO2 nanofibers were characterized by SEM. Figure 2 As shown in (a), it can be clearly seen that the surface of the nanofibers is porous after high-temperature calcination, and the average diameter is about 50-100nm. The surface porous structure can not only improve the performance of the nanofibers themselves, but also regulate the interaction between the fibers and the gas, achieving high-sensitivity detection and good selective distinction of specific gases. Figure 2 As shown in (b) and (c), the microstructure of Fe2O3-SnO2 (doped) nanofibers can be clearly seen, and the surface is porous.
[0056] Embodiment 2
[0057] Parameter Control of Temperature Modulation Technology
[0058] The present invention uses a Keithley6487 picoammeter as a voltage source and current reader, applies a membrane voltage of 5V to the transducer, and records two values per second. A square wave pulse heating voltage is applied to the resistance wire using RIGOL DP832A, and the parameters are as follows: low voltage 0V, high voltage 6.5V and 50% duty cycle; frequency adjustment range: 0.01Hz-0.05Hz. Different frequencies exhibit different temperature changes at this voltage. The sensing measurement is carried out in a closed glass container (500mL) equipped with appropriate airflow inlet and outlet. The detected gas is subjected to temperature modulated sensing behavior in dry air, and each measurement is repeated more than three times. Here, the response is defined as S=R at the characteristic temperature point. a / R g , where R a and R gThey are the resistance in dry air and in the presence of the detected gas at the corresponding characteristic temperature points. Finally, the characteristic response curve of the target gas under temperature modulation is obtained by computer data acquisition. It should be emphasized that all gas sensing measurements are performed in dry air.
[0059] Embodiment 3
[0060] n-Propanol gas-sensitive performance test
[0061] Example 3: In the present invention, a ceramic sheet is selected as the main structure of the sensor, the sensing element is mainly supported by a six-pin base, the gold electrode on the front of the heating ceramic plate is used as a test electrode, and the RuO2 resistor on the back is used as a heating electrode to provide the required working temperature for the target gas test. When manufacturing the sensor, it is necessary to select a translucent nanofiber membrane of appropriate size and thickness as the material of the gas-sensitive sensor element. In general, the differences in the materials of different gas-sensitive sensor elements are mainly reflected in their sensitive characteristics and their applications in sensor manufacturing. In practical applications, it is crucial to select suitable gas-sensitive materials according to the specific needs of the sensor. It is worth noting that in order to ensure the stability of the experiment, the sensors that have been manufactured need to be subjected to a stable aging treatment, which generally lasts for 12-24 hours under dry conditions for appropriate storage. After completing the corresponding steps, the gas sensor can perform the corresponding operation.
[0062] Static test: First, the Fe2O3-doped SnO2 nanofiber (Fe2O3-SnO2) gas sensor was tested at a temperature range of 150°C-400°C for 100ppm n-propanol. The test results are as follows: Figure 3 As shown. Figure 3 It can be clearly concluded that when the optimal temperature is 250°C, the Fe2O3-SnO2 nanofiber gas sensor has the best response to 100ppm n-propanol. Subsequently, a linear correlation test was conducted on the test gas n-propanol, and the specific results are shown in Figure 4 In the experiment, Fe2O3-SnO2 gas sensor was used to test the concentration gradient of 1, 10, 25, 50, 75, and 100 ppm n-propanol, and the corresponding response values were 4.05, 44.58, 97.06, 234.6, 319.5, and 425, respectively. At the same time, the linear relationship was calculated to a certain extent, such as Figure 4 As shown in (b), there is a specific functional relationship between the response time and the response value: y = 4.44x-7.48, and the fitting coefficient R 2 =0.99, which has a highly linear relationship. For the Fe2O3-SnO2 gas sensor at the optimal operating temperature of 250°C, its real-time response curve for 100ppm n-propanol is as follows Figure 5The results show that when the target gas comes into contact with the sensor surface, the resistance of the sensor changes significantly and decreases rapidly, and the response value also increases rapidly accordingly, and finally reaches a saturated state and tends to a stable equilibrium state. The response time of this process is 24s. When dry air is introduced again, the resistance of the sensor gradually returns to its initial state, and this recovery process takes 55s. These data clearly show that the sensor has a short response / recovery time.
[0063] Embodiment 4
[0064] Identification of n-Propanol Gas
[0065] Example 4: The output results of the Fe2O3-SnO2 (doped) sensor of the present invention for three VOCs gases (n-propanol, n-butanol, ethanol) under frequency modulation (0.01-0.05 Hz), and the corresponding response characteristic curves are obtained, such as Figure 6 Based on the above response characteristic curve test results, LDA (Linear Discriminant Analysis) is used to extract the characteristics of three gases: n-propanol, n-butanol, and ethanol. The output results are as follows: Figure 7 As shown in the figure, it can be clearly concluded that n-propanol is successfully identified under 0.02Hz frequency modulation. After specific identification of n-propanol gas, the present invention further explores the relationship between its response value and different concentrations (0.1-100ppm), as shown in the figure. Figure 8 As shown. It can be clearly found from the figure that n-propanol gas has two significant characteristic peaks at time and temperature of 53.5s (283.5℃) and 79.5s (393.6℃), and the strength of the characteristic peaks is stable within a certain concentration range. More specifically, there is a specific functional relationship between the response value of n-propanol gas and different concentrations. This functional relationship can be expressed as: y1=12.11x+5.69; y2=1.54x+0.84, and the relevant fitting coefficient R 2 =0.99, which also indirectly confirms that there is a specific linear relationship between the two.
[0066] This invention is expected to provide new material solutions and technical support for fields such as environmental monitoring, medical health and industrial safety, and has broad application prospects and far-reaching social significance.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Fe2O3-doped SnO2 nanofiber gas sensor, characterized in that: include: (1) Preparation of Fe2O3-doped SnO2 nanofibers The nanofibers are synthesized by electrospinning technology and calcined in air to obtain the nanofiber gas-sensitive material; The electrospinning solution includes a tin salt, an iron salt, and a polymer; (2) Fabrication of gas sensors Fe2O3-doped SnO2 nanofibers, namely Fe2O3-SnO 2, As gas sensing material; According to the requirements of sensitive material properties and preparation methods, six-pin nickel-chromium was selected as the sensor substrate; The sensitive material is usually deposited on the substrate in the form of a thin film; during the preparation process, parameters such as temperature, atmosphere and pressure must be controlled to ensure the uniformity and consistency of the sensitive film layer; Preparation of polar electrodes: Processing polar electrodes on the sensitive film layer to provide input and output of current and voltage; Packaging protection: Packaging the prepared sensitive components to protect the sensitive film layer from interference from the external environment and impurities; Connection and testing: Connect and fix the sensitive components to the external circuit and perform relevant tests; The testing process may involve the measurement of resistance, current and voltage, as well as the evaluation of the response to the target gas; (3) Parameter control of temperature modulation technology Including adjustment of frequency, duty cycle and voltage parameters.
2. The method for preparing a Fe2O3-doped SnO2 nanofiber gas sensor according to claim 1, characterized in that: In the electrospinning solution, the tin salt is preferably at least one of stannous chloride, stannous oxalate, tin tetrachloride or stannous sulfate; the iron salt is preferably at least one of ferric chloride, ferric sulfate and ferric nitrate; the polymer is preferably at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylonitrile or polystyrene; In the electrospinning solution, the mass ratio of the tin salt, the iron salt and the polymer is 0.6:0.5:0.9; The electrospinning solution also includes an organic solvent; The organic solvent is at least one of N,N-dimethylformamide, polyvinyl alcohol or formic acid; The voltage of the electrospinning is 16-20 kV, the distance between the needle and the collector is 10-20 cm, and the feeding speed is 0.0002-0.0004 mm / s; The calcination temperature is 450-550°C, the calcination time is 1-3h, and the heating rate is 1-3°C / min.
3. The method for preparing a Fe2O3-doped SnO2 nanofiber gas sensor according to claim 1, characterized in that: During the preparation of the element, various parameters and conditions need to be strictly controlled to ensure the stability and reliability of the sensitive performance. In addition, in order to obtain better sensing performance, the performance of the sensor element can be further improved by regulating factors such as temperature, pressure, atmosphere, etc. during the preparation process, as well as optimizing the material and structural design. Ceramic sheet is selected as the main structure of the sensor. The sensing element is mainly supported by a six-pin base. The gold electrode on the front of the heating ceramic plate is used as a test electrode, and the RuO2 resistor on the back is used as a heating electrode to provide the required working temperature for the target gas test.
4. The method for preparing a Fe2O3-doped SnO2 nanofiber gas sensor according to claim 1, characterized in that: When manufacturing the sensor, it is necessary to select a translucent nanofiber membrane of appropriate size and thickness as the material of the gas sensing element; the differences in the materials of different gas sensing elements are mainly reflected in their sensitive properties and their applications in sensor manufacturing.
5. The method for preparing a Fe2O3-doped SnO2 nanofiber gas sensor according to claim 1, characterized in that: To ensure the stability of the experiment, the manufactured sensors need to be subjected to a stable aging treatment, generally stored properly under dry conditions for 12-24 hours; after completing the corresponding steps, the gas sensor can be used for the corresponding experimental operation.
6. The method for preparing a Fe2O3-doped SnO2 nanofiber gas sensor according to claim 1, characterized in that: In the parameter control of (3) temperature modulation technique: a Keithley 6487 picoammeter was used as a voltage source and current reader, a membrane voltage of 5 V was applied to the transducer, and two values were recorded per second; A square wave pulse heating voltage was applied to the resistance wire using RIGOL DP832A, and the parameters were as follows: low voltage 0 V, high voltage 6.5 V, and 50% duty cycle; frequency adjustment range: 0.01 Hz-0.05 Hz. 7 . The gas sensor according to claim 1 , which is a n-propanol gas sensor.
8. The method for preparing a Fe2O3-doped SnO2 nanofiber gas sensor according to claim 7, characterized in that: The test method of n-propanol gas sensing performance is as follows: the sensing measurement is carried out in a closed glass container (500 mL) equipped with appropriate gas flow inlet and outlet; the temperature modulation sensing behavior of the detected gas is carried out in dry air, and each measurement is repeated more than three times; Among them, ceramic sheet is selected as the main structure of the sensor. The sensing element is mainly supported by a six-pin base. The gold electrode on the front of the heating ceramic plate is used as a test electrode, and the RuO2 resistor on the back is used as a heating electrode to provide the required working temperature for the target gas test.
9. An application of a gas sensor according to any one of claims 1 to 6, characterized in that: The gas sensor is used for identifying n-propanol gas; The identification method of n-propanol gas is: LDA (Linear Discriminant Analysis) was used; Quantitative analysis is used to identify and analyze gases.
10. The use of the gas sensor according to claim 9, characterized in that: For the sensors that have been manufactured, they need to be subjected to stable aging treatment, generally by being properly stored in dry conditions for 12-24 hours.
Citation Information
Cited By
N-propyl alcohol gas sensor based on hollow CuO / ZnO heterostructure material as well as preparation method and application of n-propyl alcohol gas sensor
CN122468794A